The Degree of Religiosity, Motivation, Islamic Personality, and Cultural Values of Software Developers and Their Relevance to Work Behavior - Utami, Meinarini Catur; Al Anziy, Misyal S; Rosyada, Dede; Suryani, Erma; Hakiem, Nashrul (JURNAL INDO-ISLAMIKA, 2024)
The use of the Internet in various fields has grownrapidly, as it makes one's activities more efficient andeffective. This necessitates the development of anapplication specific to its intended use, which in turnrequires a software developer's expertise. Indonesia hasa scarcity of software developers, a situation akin to anIT crisis that indirectly impacts software developerperformance. This study aims to determine the level ofreligiosity, motivation, Islamic personality, and culturalvalue of software developers, as well as theirrelationship to work behavior. A quantitative approachwas used, with 157 respondents from West Java, Jakarta,and Banten surveyed and 15 interviewed. The study'sfindings showed that the respondents' religiosity,motivation, Islamic personality, and cultural values hadalready entered the good category. According torespondents, there was a significant relationshipbetween religiosity, motivation, Islamic personality,cultural values, and work behavior.